Comparative Analysis of CPM and PERT Methods for Scheduling the Repair Process of KMP. Kormomolin - Ainun Jariah; Juswan Sade (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
In the maritime industry, scheduling ship repair projects is an important aspect that determines operational efficiency and navigational safety. An appropriate scheduling method can help optimize project duration and manage uncertainties that may arise during project implementation. Two commonly used methods are the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT), which apply deterministic and probabilistic approaches, respectively. This study was conducted on the repair project of KMP. Kormomolin, which had an initial planned duration of 52 days and involved 58 technical activities. The CPM method was used to identify the critical path based on fixed activity durations obtained from the repair list, while the PERT method was applied to estimate project duration using three-time estimates: optimistic, most likely, and pessimistic. The analysis was carried out using Microsoft Project and manual calculations to determine Early Finish (EF), Late Finish (LF), Total Float, and the probability of project completion. The CPM analysis showed that the project could be completed within 48 days, with a critical path consisting of activities with no slack. Meanwhile, the PERT method produced an estimated project duration of 50 days, with a completion probability of 95.82%. The CPM method provides stricter time control, whereas PERT offers greater flexibility in dealing with uncertainty. CPM is more suitable for projects with a stable work structure and clear activity sequences, while PERT is more appropriate for projects involving many variables and risks. The integration of both methods is recommended to produce more adaptive and comprehensive project planning in the ship repair industry.